Biomass-derived carbon nanomaterials for sensor applications - Malode S.J.; Shanbhag M.M.; Kumari R.; Dkhar D.S.; Chandra P.; Shetti N.P. (My University, 2025)
In recent years, an increasing amount of attention has been paid to utilizing dedicated waste biomass as a sustainable, cheap, and abundant fuel and material source. There is a tremendous opportunity for maximizing energy production by applying different reliable waste biomass as a renewable, affordable, and excellent resource. As a result of renewable hydrocarbons such as biomass, bioenergy is produced, green chemicals are manufactured, and carbon materials are made. Furthermore, biomass can be utilized as a source of advanced carbon materials. Carbon materials derived from biomass can also be used to support catalysts in fuel cells with polymer electrolyte membranes. For the fabrication of electrochemical sensors, porous carbonaceous materials generated from biomass are highly advised owing to their specific qualities, including regenerative nature, affordability, distinctive structure, and sustainability. The surface morphology of the sensor, especially its pore volume, surface area, and pore size affects both its electrochemical and catalytic activity. Metal nanoparticle activation, doping, and dispersion are just a few of the methods that may be used to improve the performance of sensors. To detect a variety of target analytes, such as biomolecules, metal ions, contaminants, food additives, and flavonoids, some of the key or seminal advances in the field of biomass-derived carbonaceous compounds are discussed. The materials and composites made of biomass-derived carbon will be in-depth examined, evaluated, and compared in this review. The associated technological difficulties are also discussed, and future research areas are suggested for use in practical applications. Nano carbon materials have several integrated advantages, including good electrical conductivity, structural and chemical flexibility, reduced chemical functionalization, and bulk production potential, making them viable candidates for various electrochemical processes. In the coming years, bio-carbon production from waste biomass is expected to gain rapid scientific and industrial interest because it will be used in electrochemical devices and rechargeable batteries. We emphasize the variety of waste biomass precursors that are accessible, as well as the recent developments in the manufacture of bio-carbon. Carbonaceous nanoparticles generated from biomass have shown potential for use in fuel cells, bioimaging, medicinal delivery, carbon fixation, catalysis, and gas sensors. Interestingly, this article has covered these nanomaterials' new and innovative energy conversion and storage services. Finally, the remaining difficulties, perspective views, and potential research trajectories in the area are described. © 2022 Elsevier B.V.